DOI: 10.33915/etd.7039
|View full text |Cite
|
Sign up to set email alerts
|

Developing high performance and stable hetero-structured cathodes and fundamental understanding of oxygen reduction and reaction behavior

Abstract: Developing High Performance and Stable Hetero-structured Cathodes and Fundamental Understanding of Oxygen Reduction and Reaction Behavior ByXinxin Zhang New hetero-structured La2NiO4+δ (LNO)/ (La0.6Sr0.4)0.95Co0.2Fe0.8O3-δ (LSCF) SOFC cathodes have been successfully fabricated by the infiltration technique for long-term stability and oxygen reduction reaction (ORR) kinetic consideration. The current comparative study of LSCF and LNO-infiltrated LSCF shows a significant reduction in polarization resistance by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 91 publications
(98 reference statements)
3
6
0
Order By: Relevance
“…The results of calculations done assuming phase-pure La 2– x NiO 4+δ compositions for the entire series (Figure A) showed that the total oxygen content 4+δ decreases nearly linear with the nominal x . If the materials were indeed single-phase, this would indicate that the increase in the concentration of cation vacancies in the lanthanum sublattice is mainly compensated by a change in the concentration of oxygen defects  a decrease in the concentration of interstitial oxygen, followed by a transition to oxygen deficiency and an increase in the concentration of oxygen vacancies for x = 0.10, in accordance with eq and conclusions in selected literature sources. ,, …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The results of calculations done assuming phase-pure La 2– x NiO 4+δ compositions for the entire series (Figure A) showed that the total oxygen content 4+δ decreases nearly linear with the nominal x . If the materials were indeed single-phase, this would indicate that the increase in the concentration of cation vacancies in the lanthanum sublattice is mainly compensated by a change in the concentration of oxygen defects  a decrease in the concentration of interstitial oxygen, followed by a transition to oxygen deficiency and an increase in the concentration of oxygen vacancies for x = 0.10, in accordance with eq and conclusions in selected literature sources. ,, …”
Section: Resultssupporting
confidence: 87%
“…The noted trends in the relevant properties with increasing nominal A-site deficiency included a minor increase in electrical conductivity (shown only for selected compositions), a gradual decrease in the roomtemperature oxygen content with a transition to oxygen deficiency, and a progressive increase in the polarization resistance of La 2−x NiO 4+δ electrodes. 27,28 Similar inconsistencies can be found in available literature reports on A-site-deficient nickelates derived from Nd 2 NiO 4+δ 29−37 and Pr 2 NiO 4+δ . 38−47 The following communications are worth highlighting, among others, in the context of the present work.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations